Evaluating the Link Between Environmental Awareness and Related Behavioural Anxiety With State and Trait Anxiety - Juneja, Surbhi (My University, 2023)
The true value of the environment is something we cannot comprehend. However, we may make some educated guesses about its significance that will aid in our comprehension of it. Humans cause environmental degradation, and have borne the effects of these causes. The most common impact of this degradation faced by individuals nowadays is Anxiety. Simply put, anxiety is, feelings of dread, worry, and unease that could develop in response to stress. In the current study, the research aimed to study the effect of anxiety and eco-anxiety using the New Ecological Paradigm as well as HOGG anxiety scale on individuals. The New Ecological Paradigm endorses a “pro-ecological” worldview. The Dominant Social Paradigm which is the contrasting part of the NEP Scale, comprises of the view that humans are superior to all other species, the Earth provides unlimited human resources, and that progress is an inherent part of human history. The individuals' State Anxiety- Trait anxiety, Eco Anxiety, New Ecological Paradigm, and Dominant Social Paradigm were measured, and associations among these were explored. It was hypothesised that high levels of state-trait anxiety would modulate environmental concerns. The results reveal high correlation is seen among state- Trait Anxiety and HOGG and Trait Anxiety is correlated with NEP.
Keywords: Eco-anxiety; State Anxiety; Trait Anxiety; New ecological Paradigm; Dominant Social Paradigm